Faktor yang Memengaruhi Kepatuhan Minum Obat Antihipertensi pada Lansia (Journal of Telenursing (JOTING), 2024)
This study aims to review previous studies related to adherence to taking antihypertensive medication in elderly hypertensive patients to determine the factors that influence the adherence of elderly people suffering from hypertension who consume antihypertensive medicines. The method used is the scoping review analysis method. Article searches using databases from Scopus, Wiley, and Semantic Scholar with a research period from 2019 to 2024, with the keywords "factor" AND "adherence" AND "medication" AND "hypertension" AND "older" OR "adult". The articles are in full-text form, accessible, in English, limited to the last 6 years, and no country restrictions, and discuss adherence to taking antihypertensive medication in the elderly. The results showed that 6 articles met the inclusion criteria after going through the selection process. All articles used quantitative methods and came from the United States (2 articles), China (1 article), Thailand (1 article), Brazil (1 article), and Korea (1 article). The average age of participants was between 65-80 years and above. Factors that influence compliance with taking antihypertensive medication in the elderly. In conclusion, factors that influence compliance with taking antihypertensive medication in the elderly with hypertension consist of the elderly's factors (intrinsic factors) and other factors (extrinsic factors). Keywords: Factors, Hypertension, Compliance with Taking Medication, Elderly